Crystal Structure of the DFNKF Segment of Human Calcitonin Unveils Aromatic Interactions between Phenylalanines. Issue 9 (16th December 2016) - Bertolani, Arianna; Pizzi, Andrea; Pirrie, Lisa; Gazzera, Lara; Morra, Giulia; Meli, Massimiliano; Colombo, Giorgio; Genoni, Alessandro; Cavallo, Gabriella; Terraneo, Giancarlo; Metrangolo, Pierangelo
Abstract: Invited for the cover of this issue is the group of Pierangelo Metrangolo at the Politecnico di Milano. The image depicts the steric zipper formed by the amyloidogenic peptide, DFNKF. Read the full text of the article at10.1002/chem.201604639 . Abstract : " To obtain the reported crystal required six months, and the crystals were tiny… " Read more about the story behind the cover in the Cover Profile and about the research itself on page 2051 ff. (DOI:10.1002/chem.201604639 ).